Contramajoritário, representativo e iluminista: os papéis das supremas cortes e tribunais constitucionais nas democracias contemporâneas - Luís Roberto Barroso (Revista Interdisciplinar de Direito, 2018)
The primary purpose of this Article is to examine the roles of constitutional courts in contemporary democracies. It aims to demonstrate that such courts perform, in addition to the counter-majoritarian role traditionally recognized in constitutional theory, two other roles: representative and, occasionally, enlightened. In the construction of the argument, the essay analyzes the phenomena of the judicialization of politics and judicial activism, as well as the issue of the difficult demarcation of the border between law and politics in the complex and plural societies of today. Although it presents several examples of the constitutional experience of the United States, the Article’s conclusions are generalizable, looking at the roles of constitutional courts from the perspective of a global constitutionalism whose categories have become common practice in the democracies of the world.